ABL1 in thalamus is associated with safety but not fear learning - Habib, Mouna R.; Ganea, Dan; Katz, Ira K.; Lamprecht, Raphael (Frontiers in Systems Neuroscience, 2013)
In auditory fear conditioning a tone is paired with a footshock, establishing long lasting fear memory to the tone. In safety learning these stimuli are presented in an unpaired non-overlapping manner and enduring memories to the tone as a safety signal are formed. Although these paradigms utilize the same sensory stimuli different memories are formed leading to distinct behavioral outcome. In this study we aimed to explore whether fear conditioning and safety learning lead to different molecular changes in thalamic area that receives tone and shock inputs. Toward that end, we used antibody microarrays to detect changes in proteins levels in this brain region. The levels of ABL1, Bog, IL1B and Tau proteins in thalamus were found to be lower in the group trained for safety learning compared to the fear conditioning group 6 hrs after training. The levels of these proteins were not different between safety learning and fear conditioning trained groups in auditory cortex. Western blot analysis revealed that the ABL1 protein level in thalamus is reduced specifically by safety learning but not fear conditioning when compared to naïve rats. These results show that safety learning leads to activation of auditory thalamus differently from fear conditioning and to a decrease in the level of ABL1 protein in this brain region. Reduction in ABL1 level in thalamus may affect neuronal processes, such as morphogenesis and synaptic efficacy shown to be intimately regulated by changes in this kinase level.